2019
DOI: 10.1371/journal.pgen.1008022
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bacterial surface attachment by a network of sensory transduction proteins

Abstract: Bacteria are often attached to surfaces in natural ecosystems. A surface-associated lifestyle can have advantages, but shifts in the physiochemical state of the environment may result in conditions in which attachment has a negative fitness impact. Therefore, bacteria employ numerous mechanisms to control the transition from an unattached to a sessile state. The Caulobacter crescentus protein HfiA is a potent developmental inhibitor of the secreted polysaccharide adhesin known as the hol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 74 publications
(112 reference statements)
3
54
0
Order By: Relevance
“…Transcription of hfiA is finely tuned by a complex hierarchy of transcription factors such that small changes in expression have significant impacts on holdfast production (33,35,37). The three nonadhesive mutants analyzed in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcription of hfiA is finely tuned by a complex hierarchy of transcription factors such that small changes in expression have significant impacts on holdfast production (33,35,37). The three nonadhesive mutants analyzed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, P hifA -lacZ activity differences for other key strains are modest and do not correlate perfectly with direct measurements of holdfast production. While cell cycle control and posttranscriptional processes can be masked in bulk reporter measurements, the expression level changes in flagellar signaling mutants are less pronounced than for regulatory systems that target hfiA directly (35,37). A significant portion of adhesion control exerted by the flagellum likely occurs independently of hfiA regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holdfast biogenesis is also influenced by mechanical cues [18-20], while the second messenger cyclic-di-GMP affects both synthesis [19] and physical properties of [21] the holdfast. Additionally, an elaborate regulatory pathway comprised of multiple two-component signaling (TCS) proteins and one-component regulators controls holdfast development and surface attachment [16]. We have previously shown that a C. crescentus strain expressing a non-phosphorylatable allele of the lovK sensor histidine kinase ( lovK H180A ) overproduces holdfast and, consequently, has an enhanced adhesion phenotype in a biofilm assay.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that a C. crescentus strain expressing a non-phosphorylatable allele of the lovK sensor histidine kinase ( lovK H180A ) overproduces holdfast and, consequently, has an enhanced adhesion phenotype in a biofilm assay. The lovK H180A adhesion phenotype requires the presence of spdS-spdR two-component system genes and the hybrid histidine kinase skaH gene [16]. Two XRE-family transcription factors, RtrA and RtrB, function downstream of the TCS regulators to promote holdfast synthesis by directly repressing transcription of the holdfast inhibitor, hfiA (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%